2001
DOI: 10.3346/jkms.2001.16.4.522
|View full text |Cite
|
Sign up to set email alerts
|

MR Findings of the Spinal Paraganglioma: Report of Three Cases

Abstract: Extraadrenal paragangliomas involving the spine is less common and usually takes the form of intradural compression of the cauda equina. The authors report three cases of spinal paragangliomas resulting in extradural spinal cord compression and their MR findings. The MR imaging revealed a well-demarcated extradural mass with low to intermediate signal intensity on T1-weighted images and intermediate to high signal intensity on T2-weighted images compared to paravertebral muscles. After Gd-DTPA administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…Preoperative embolisation reduces tumour vascularity, allowing more complete resection and a lower morbidity rate in patients with hypervascular tumours. The authors of previous reports have shown efficacy for renal and non-renal spinal metastases such as melanoma, sarcoma, thyroid, breast, prostate, hepatic carcinoma, and neuroendocrine tumours such as paragangliomas [6][7][8][9][10][11][12][13]. Nevertheless, the amount of blood loss is variable [13,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative embolisation reduces tumour vascularity, allowing more complete resection and a lower morbidity rate in patients with hypervascular tumours. The authors of previous reports have shown efficacy for renal and non-renal spinal metastases such as melanoma, sarcoma, thyroid, breast, prostate, hepatic carcinoma, and neuroendocrine tumours such as paragangliomas [6][7][8][9][10][11][12][13]. Nevertheless, the amount of blood loss is variable [13,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…an estimate of the extent of tumour blush visible after treatment. The grading scale used in this study was similar to that used by others, including the very experienced unit in Memorial SloanKettering, New York [7,13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Areas of osteolysis or even pathological fractures and/or enlargement of the vertebral foraminae are often observed. 1,13,15 Osteocondensant forms have rarely been described and may also be found in the adjacent costs. 12 On MRI, paragangliomas appear hypo-iso-intense on T 1 and iso-hyper-intense, often with a 'salt & pepper' appearance on T 2 -weighted images.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…[1][2][3][4][5][6] Findings in the extradural space at a cervical or dorsal spinal level are particularly rare. 1,3,4,[7][8][9][10][11][12][13][14][15] We describe the case of a thoracic extradural paraganglioma invading the thoracic cavity. A revision of the literature is reported.…”
Section: Introductionmentioning
confidence: 99%